2018
DOI: 10.3389/fpsyg.2018.00184
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Attention-to-Memory Depends on the Interplay of Memory Capacity and Memory Load

Abstract: Humans can be cued to attend to an item in memory, which facilitates and enhances the perceptual precision in recalling this item. Here, we demonstrate that this facilitating effect of attention-to-memory hinges on the overall degree of memory load. The benefit an individual draws from attention-to-memory depends on her overall working memory performance, measured as sensitivity (d′) in a retroactive cue (retro-cue) pitch discrimination task. While listeners maintained 2, 4, or 6 auditory syllables in memory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 47 publications
2
17
1
1
Order By: Relevance
“…Baddeley, 1992Baddeley, , 2003, but rather that these working memory representations retain the indexical variability of speech encountered during encoding. That is, as stimulus-specific details of speech are internally represented in memory (Lim et al, 2015(Lim et al, , 2018, speech spoken by one consistent talker might be more efficiently represented in working memory than speech spoken by different talkers, even if the speech carries the same linguistic message (see below for a discussion of potential differences in memory representations). This possibility is consistent with an emerging neurobiological model of speech working memory, which posits that maintenance of speech information in memory relies on the very same brain networks involved in speech perception and production (Hickok, 2009;Jacquemot & Scott, 2006;Perrachione, Ghosh, Ostrovskaya, Gabrieli, & Kovelman, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baddeley, 1992Baddeley, , 2003, but rather that these working memory representations retain the indexical variability of speech encountered during encoding. That is, as stimulus-specific details of speech are internally represented in memory (Lim et al, 2015(Lim et al, , 2018, speech spoken by one consistent talker might be more efficiently represented in working memory than speech spoken by different talkers, even if the speech carries the same linguistic message (see below for a discussion of potential differences in memory representations). This possibility is consistent with an emerging neurobiological model of speech working memory, which posits that maintenance of speech information in memory relies on the very same brain networks involved in speech perception and production (Hickok, 2009;Jacquemot & Scott, 2006;Perrachione, Ghosh, Ostrovskaya, Gabrieli, & Kovelman, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The classic working memory model asserts that the contents of working memory are abstract representations of linguistic units (Baddeley, 1992), which would suggest processing time should affect working memory and long-term memory similarly. However, recent studies have demonstrated that stimulus-specific acoustic details (e.g., syllable pitch) are also maintained in working memory (Lim, Wöstmann, & Obleser, 2015;Lim, Wöstmann, Geweke, & Obleser, 2018). This raises the possibility that talker variability during perceptual processing will also influence auditory working memory representations, and will do so in a manner similar to how it affects immediate speech recognition.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to pre-cues, a single informative retro-cue did not improve the precision of recalled items; although similar to pre-cues, it did improve the probability of an item to be recalled (lower guess rate) (Murray, Nobre, Clark, Cravo, & Stokes, 2013). Other studies have demonstrated that informative retro-cues improved both the speed of recall and the precision of the memory report for auditory pitch, suggesting retro-cues may benefit auditory memory performance in a similar manner as pre-cues (Lim, Wöstmann, Geweke, & Obleser, 2018). Gunseli, van Moorselaar, Meeter, & Olivers, (2015) manipulated the validity of retro-cues, demonstrating that the precision and recall probability differ between cues with 50% and 80% validity (Gunseli et al, 2015).…”
Section: Are Memory Resources Flexible After Encoding?mentioning
confidence: 78%
“…Another explanation may be that utilizing retro-cues is very effortful, which may interfere with maintaining multiple items in memory. Lim et al, (2018) reported that a retro-cuing benefit to auditory precision was more reliable in high-capacity subjects, suggesting that processing a retro-cue itself was cognitively demanding. Thus, it may be that multiple items do not experience a retro-cue benefit because it is too cognitively demanding.…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed to explain this discrepancy. Recent research (Lim, Wöstmann, Geweke, & Obleser, 2018), for example, showed that the effectiveness of attentional refreshing was contingent upon the interplay of task loads and individual differences in working memory capacity for syllables. Our Experiment 2 and Experiment 1 seemed to differ in task difficulty (and thus the cognitive load imposed), so further examinations of attentional refreshing across different cognitive loads may offer a useful avenue for future research.…”
Section: Theoretical Implicationsmentioning
confidence: 99%